PENGARUH GAYA HIDUP, LOKASI DAN SERVICESCAFE TERHADAP KEPUASAN KONSUMEN DI KEDAI KOPI NIPAH PADANG - Primutia Ananda; Maria Magdalena (LP2M Universitas Bina Bangsa, 2024)
Consumer satisfaction is a person's feeling of joy or disappointment that arises from comparing the product's perceived performance (or results) to their expectations of the actions taken by the consumer. The research aims to test whether the influence of lifestyle, location and cafe services has an effect on consumer satisfaction at Padang nipah coffee shops. The data source used in this research is primary data. The population in this observation was visitors to the Nipah coffee shop, totaling 2,393 people. This sampling technique is incidental sampling. The number of samples used in this research was 96 people. The analytical method used is multiple regression analysis. The conclusion of this research is that the influence of lifestyle (X1) has a positive and significant influence on consumer satisfaction, location (X2) has a positive and significant influence on consumer satisfaction, and service cafes (X3) have a positive and significant influence on consumer satisfaction